DDRE-48. COMPARTMENT LOCKED IL-12 - INCREASED TISSUE RETENTION AND MINIMAL PERIPHERAL EXPOSURE ALLOW HIGHER TREATMENT EFFICACY AND TOLERABILITY IN LOCAL GLIOBLASTOMA THERAPY. (12th November 2021) - Beffinger, Michal; Schellhammer, Linda; Shekarian, Tala; Deplazes, Sereina; Zimmermann, Ivan; Egloff, Pascal; Buch, Thorsten; Seeger, Markus; Hutter, Gregor; Vom Berg, Johannes
Abstract: Recent clinical studies in glioblastoma (GBM) highlight the potential of local IL-12 therapy, but they also bring back tolerability concerns due to leakage into the periphery. This leakage might thus hamper exploiting the full potential of local IL-12 therapy. Fusion with an IgG4 Fc portion increases the tissue retention of IL-12; but could also confer export into the blood and subsequent systemic recycling through the neonatal Fc receptor (FcRn), ultimately leading to potentially toxic IL-12 serum levels. We assessed the expression of FcRn in human and murine GBM and its role in IL-12Fc tissue retention and systemic exposure upon local delivery. Human or murine IL-12Fc was injected in GBM-bearing or naïve wt or FcRn-humanized mice continuously or as bolus via convection-enhanced delivery (CED). We screened combinations of amino-acid substitutions at the (IL-12)Fc:FcRn binding interface to abolish this interaction. Brain and blood concentrations were assessed via ELISA or cytokine bead arrays. FcRn affinity was measured by SPR/ELISA and bioactivity tested on PBMCs and human GBM explant cultures. Treatment efficacy and immunological correlates were assessed in GBM bearing mice. FcRn is upregulated in human and mouse GBM and contributes to brain export and subsequent peripheral recycling of IL-12Fc in the blood. IL-12Fc with abrogated FcRn binding due to a unique set of substitutions is fully functional and appears brain compartment locked (CL IL-12) as it exhibits enhanced tissue retention and reduced serum levels upon local injection, reaching up 100x higher brain to serum concentration ratios than regular IL-12. Compared to its non-modified counterpart, murine CL IL-12 shows significantly higher treatment efficacy at negligible systemic footprint in late stage murine GBM. In patient explant cultures, human CL IL-12 leads to successful inflammatory conditioning. Compartment locked IL-12 should thus allow a wide dosing window to fully harness its therapeutic potential for local GBM therapy.